1992
DOI: 10.1161/01.str.23.9.1257
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphism of the apoprotein A-I-C-III gene cluster in control and stroke-prone white and black subjects: racial differences.

Abstract: Background and Purpose:The presence of known restriction fragment length polymorphisms in the apoprotein A-I-C-III gene cluster, which encodes their respective apoproteins, was investigated using the restriction enzymes Sac I and Pst I to determine the potential role of genetic variations for stroke risk in an American population.Methods: Ninety-eight subjects (70 white, 28 black subjects), both normal controls with no carotid stenosis and those with carotid stenosis believed at risk for stroke, defined as sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…More recent studies have shown an association between dyslipidemic states and cerebrovascular disease. 61 - 62 We found that a history of previously diagnosed dyslipidemia was significantly more prevalent among the stroke population than the control subjects and was an independent risk factor in the multivariate analysis. A detailed report of the lipid profiles of the patients and control subjects is being prepared.…”
Section: -59mentioning
confidence: 80%
“…More recent studies have shown an association between dyslipidemic states and cerebrovascular disease. 61 - 62 We found that a history of previously diagnosed dyslipidemia was significantly more prevalent among the stroke population than the control subjects and was an independent risk factor in the multivariate analysis. A detailed report of the lipid profiles of the patients and control subjects is being prepared.…”
Section: -59mentioning
confidence: 80%
“…52 Another explanation for the effect of alcohol on the risk of stroke is the finding that alcohol increases HDL cholesterol levels, 53,54 which are inversely related to arteriosclerosis at many sites, including the carotid arteries. 41,55 HDL cholesterol levels are lower in survivors of stroke than in controls. [56][57][58] However, changes in HDL cholesterol levels only partially explain the inverse relation between alcohol consumption and death from cardiovascular causes.…”
Section: Discussionmentioning
confidence: 94%
“…Whether the dynamic process of plaque formation at the carotid bifur cation is due to lipid or coagulation/plalelet aggregation defects, Grolta et al [25] reported a significant increase in carotid stenosis of 2:23% over 30 m on th s was associated with a significant increase in LD L. In addition, evaluation of the dynamic aspects of L D L and IID L metabolism by assessing in vivo metabolism o f autologously labelled lipoproteins demonstrated a slower catabolism of LD L and a faster one for I IDL, suggesting that increased resi dent lime in serum combined with enhanced catabolism of H D L is associated with ABls [26], In addition to metabolic parameters supporting the role o f impaired or abnormal cholesterol transport in ABls, altered gene function for proteins involved in cho lesterol metabolism may likely play an important role in determining ABI susceptibility. For example, in a study of gene polymorphism o f the major apoprotein of I IDL, Kasturi et al [27] reported on the occurrence of restric tion fragment length polymorphism (RFLP) of the tandemly arranged apoproteins of A l, ( 'III, and AIV on the long arm o f chromosome 11. Results of the study demon strated that black subjects with extracranial occlusive dis ease display significant R FLP, although while subjects did not.…”
Section: Investigations On Abi: Multiple Factorsmentioning
confidence: 99%